PENGEMBANGAN METODE AS-SYAFI’I DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QURAN DI DESA PABUARAN BOGOR - Siskha Putri Sayekti; Muhammad Hikmah Rizki; Aulia Zahra; Nur’afifah Djaelani; Hasniar Hasniar; Rifa Awalia Rizki; Muhammad Syahrul Ramadhan (Institut Madani Nusantara, 2023)
This community service activity provides training in order to improve the quality of reading and writing the Qur'an using the Asy-Syafi'I method. The purpose of this community service is to improve and knowledge of teachers at TPQ Umu Hasna and TPQ Al faith in teaching reading and writing the Qur'an. Furthermore, it provides learning and introduction to students on how to easily read and write the Qur'an. The methods used in this PKM-KKN community service include planning, implementation, and monitoring and evaluation. With the implementation of this training, it is hoped that students and teachers can increase their knowledge and insights related to Quran learning methods, such as the Ash-Shafi'I method. The results of this community service can be seen from the increased knowledge of teachers with the Ash-Shafi'I method. The Ash-Shafi'I method is a way that makes it easier for people to learn how to read the Qur'an.